Performance Analysis of National Highways Public Private Partnerships in India. (July 2015) - Gopalkrishna, Nagesha; Karnam, Gayithri
The increasing choice of public private partnerships (PPPs) in infrastructure projects is due to its inherent promise to create value for money (VfM) by providing timely and improved quality of services cost effectively. This article makes an attempt to assess the performance of four national highways (NH) PPP projects in the State of Karnataka. Framework for the evaluation of the projects under review includes time overrun analysis, risk responsibility matrix, and estimation of both quantitative and qualitative VfM, that is, the financial savings to the government and road users. The study finds that the Projects 1, 3, and 4 under review created positive VfM to government (financial savings) to the tune of Rs. 1, 040 crore. VfM has also been observed to be positive to the road users by way of average reduction in travel time, saving of fuel, consistency in reaching the destination, and so on. The article also provides suggestions to tone up the PPP policy of India.